2022
DOI: 10.1126/scitranslmed.abi7282
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced piezoelectric stimulation for cartilage regeneration in rabbits

Abstract: A biodegradable piezoelectric scaffold excited by exercise promotes chondrogenesis and cartilage regeneration in rabbit osteochondral defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(97 citation statements)
references
References 67 publications
6
91
0
Order By: Relevance
“…For instance, we previously manufactured a piezoelectric zinc oxide nanogenerator scaffold for enhancing motor recovery and neural function, and implantation of zinc oxide/PCL incorporated treadmill practice provided biomimetic microenvironment and promoted nerve regeneration 18 . A similar design was also applied in the area of articular cartilage repair through PLLA nanofiber-induced piezoelectric effect 174 , further supporting the wide in vivo application of piezoelectric scaffolds. In addition, the study carried out by Chen et al .…”
Section: Biomechanics-based Tissue Engineering Strategies For Pni Man...mentioning
confidence: 74%
“…For instance, we previously manufactured a piezoelectric zinc oxide nanogenerator scaffold for enhancing motor recovery and neural function, and implantation of zinc oxide/PCL incorporated treadmill practice provided biomimetic microenvironment and promoted nerve regeneration 18 . A similar design was also applied in the area of articular cartilage repair through PLLA nanofiber-induced piezoelectric effect 174 , further supporting the wide in vivo application of piezoelectric scaffolds. In addition, the study carried out by Chen et al .…”
Section: Biomechanics-based Tissue Engineering Strategies For Pni Man...mentioning
confidence: 74%
“…This batteryless electrostimulation could promote protein adsorption and cell migration or recruitment, as well as induce endogenous TGF-β, thereby improving cartilage formation and cartilage regeneration. Rabbits with severe osteochondral defects regenerated hyaline cartilage and achieved complete cartilage healing after 1 to 2 months of self-driven electrical stimulation therapy [93]. This in situ electrical stimulation based on PENGs paves the way for smart scaffold design and future bioelectronic therapies.…”
Section: Cell Traction-driven Pengs For Cell Modulationmentioning
confidence: 92%
“…Both TENGs and PENGs have the advantages of small size, flexibility and good biocompatibility. To date, many wearable and implantable EMNGs have been reported that can efficiently harvest mechanical energy from living organisms, such as from joint motion, heartbeat and respiration, which have laid the foundation for further bioelectronic implants, especially for bones, hearts and muscles with abundant mechanical activities [93,95]. With the current progress and huge development space, EMNGs show tremendous potential for cell modulation and biomedical therapeutics.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Mechanical force from the organism itself (e.g., joint bending and body motions during walking) is a good source to activate piezoelectric polymeric nanofibers in vivo. Piezoelectric nanofibrous webs have been implanted onto the tendon to scavenge mechanical force from joint bending [62,84] or transferred into subcutaneous skin to sense motion force from walking and exercise [85]. It was demonstrated that a 6 μA of current can be detected under cyclic pulling of the mouse leg when the PVDF-TrFE nanofibrous web was placed in the subcutaneous thigh region [85].…”
Section: Cell Traction Forcementioning
confidence: 99%